If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -2n = 23 Solving 7 + -2n = 23 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2n = 23 + -7 Combine like terms: 7 + -7 = 0 0 + -2n = 23 + -7 -2n = 23 + -7 Combine like terms: 23 + -7 = 16 -2n = 16 Divide each side by '-2'. n = -8 Simplifying n = -8
| 13+4n=-91 | | -3y+6=4y+9 | | 3r+-2(5.76)=9 | | 11-5n=19 | | 3r-2(5)=9 | | 7+3n=52 | | 12-10n=-28 | | 9+-8n=-7 | | 2x+7y=22 | | 15+2n=-23 | | y^2+5y+4=0 | | 3(x+1)=22 | | 5x-20=45 | | 5y+3x=0 | | 5(5x+3)10=x+(7x)+2 | | 5(5x+3)10=x+(7x)-2 | | 5(5x+3)10=x+(5+7x)-2 | | 5(5x+3)10+7=x+(5+7x)-2 | | 5(5x+3)10+7=3x+(5+7x)-2 | | 5(5x+3)2+7=3x+(5+7x)-2 | | x+(x+1)x=22 | | X^2+60x-52000=0 | | 5(5x+3)2+7=3x+5+7x-2 | | 5(5x+3)2+7=3x+5-7x-2 | | 5(2x+3)2+7=3x+5-7x-2 | | x^2-11X+1=0 | | x+(x+1)=155 | | x^2+14x-1=0 | | 5(m+2)+3(m+7)= | | (3t-1)=(t+1) | | x^2-4x-27=0 | | 4(4c-1)-2=14c+4 |